2022
DOI: 10.1186/s41935-022-00315-0
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide intoxication: systematic literature review and proposal of new diagnostic possibilities

Abstract: Background Nitrous oxide (N2O), also called “laughing gas,” is the most commonly used inhalation anesthetic in dentistry. The N2O is no longer used, because of the long-term neurologic and cardiovascular sequelae. Due to its sedative and euphoric properties, N2O is often used for recreational use or in some erotic activities. Accidental deaths are mainly associated with the uses of N2O: death can occur from sudden cardiac arrhythmia or, most commonly, acute asphyxiation due to hypoxia. This pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 86 publications
1
2
0
Order By: Relevance
“…nNOS and iNOS are mainly associated with deleterious effects on the brain [31,33,34]. Specifically, murine experiments showed that nNOS is activated immediately after reperfusion, while iNOS is upregulated several hours after the asphyctic injury [34]. This notion is consistent with our finding about the highest expression of iNOS in the cortex of those babies undergoing intrauterine death.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…nNOS and iNOS are mainly associated with deleterious effects on the brain [31,33,34]. Specifically, murine experiments showed that nNOS is activated immediately after reperfusion, while iNOS is upregulated several hours after the asphyctic injury [34]. This notion is consistent with our finding about the highest expression of iNOS in the cortex of those babies undergoing intrauterine death.…”
Section: Discussionsupporting
confidence: 90%
“…NOS exists in three principal isoforms: endothelial (eNOS), neuronal (nNOS), and inducible NOS (iNOS). nNOS and iNOS are mainly associated with deleterious effects on the brain [31,33,34]. Specifically, murine experiments showed that nNOS is activated immediately after reperfusion, while iNOS is upregulated several hours after the asphyctic injury [34].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are few articles in the literature describing lethal N 2 O poisoning. Cipolloni et al [ 31 ] resumed the evidence finded in cases of N 2 O intoxication, reported in Table 2 .…”
Section: Discussionmentioning
confidence: 99%